To Approach or Avoid: An Introductory Overview of the Study of Anxiety Using Rodent Assays - La-Vu, Mimi; Tobias, Brooke C.; Schuette, Peter J.; Adhikari, Avishek (Frontiers in Behavioral Neuroscience, 2020)
Anxiety is a widely studied phenomenon in behavioral neuroscience, but the recent literature lacks an overview of the major conceptual framework underlying anxiety research to introduce young researchers to the field. In this mini-review article, which is aimed toward new undergraduate and graduate students, we discuss how researchers exploit the approach-avoidance conflict, an internal conflict rodents face between exploration of novel environments and avoidance of danger, to inform rodent assays that allow for the measurement of anxiety-related behavior in the laboratory. We review five widely-used rodent anxiety assays, consider the pharmacological validity of these assays, and discuss neural circuits that have recently been shown to modulate anxiety using the assays described. Finally, we offer related lines of inquiry and comment on potential future directions.